2020
DOI: 10.1007/s10212-020-00501-5
|View full text |Cite
|
Sign up to set email alerts
|

The relation between teacher self-reported individualization and student-perceived teaching quality in linguistically heterogeneous classes: an exploratory study

Abstract: Germany historically responded to student diversity by tracking students into different schools beginning with grade 5. In the last decades, sociopolitical changes, such as an increase in “German-as-a-second-language” speaking students (GSL), have increased diversity in all tracks and have forced schools to consider forms of individualization. This has opened up the scientific debate in Germany on merits and limitations of individualization for different student groups within a tracked system and heterogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…The present paper considers personalization as an educational interaction focused on student interests, activity, and initiative, as well as the reflective position of the teacher. Therefore, there may be a different relationship between the behavioral components of personalization, the orientations and sub-aspects of the quality of learning due to the Small number of studies devoted to the issue (Hachfeld & Lazarides, 2020). Our analysis was based on the assumptions that personalized learning strategies in modern vocational education play a huge role as they affect academic performance and student motivation.…”
Section: Research Question and Problem Statementmentioning
confidence: 99%
“…The present paper considers personalization as an educational interaction focused on student interests, activity, and initiative, as well as the reflective position of the teacher. Therefore, there may be a different relationship between the behavioral components of personalization, the orientations and sub-aspects of the quality of learning due to the Small number of studies devoted to the issue (Hachfeld & Lazarides, 2020). Our analysis was based on the assumptions that personalized learning strategies in modern vocational education play a huge role as they affect academic performance and student motivation.…”
Section: Research Question and Problem Statementmentioning
confidence: 99%
“…These variables likely moderate the relations between the constructs under investigation in the present study. Previous research has shown that the cognitive and motivational composition of the classroom (e.g., classes with high vs. low average achievement levels) may relate to students’ perceptions of teaching practices (Fauth et al, 2021; Hachfeld & Lazarides, 2021) and that resources and demands in schools are relevant for the relations between teacher motivation and (self-reported) teaching practices (Collie, 2021; Lazarides et al, 2020). Future research is advised to consider these and other relevant context variables.…”
Section: Discussionmentioning
confidence: 99%
“…Second, and more importantly, the tutoring modes in CAI ensure structured support adapted to each student’s learning pace [ 82 ]. This entails more regular feedback than in IBL simply because teachers working with large classes have limited time and attention, making it difficult to support each student individually [ 83 ]. Although student peers may provide some degree of feedback during IBL, the quality of this feedback may not be as valid and reliable as a teacher’s expert feedback [ 84 ].…”
Section: Discussionmentioning
confidence: 99%